Incentives for energy efficiency in the EU Emissions Trading Scheme - Joachim Schleich; Karoline S. Rogge; Regina Betz (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2008)
This paper explores the incentives for energy efficiency induced by the European Union Emissions Trading Scheme (EU ETS) for installations in the energy and industry sectors. Our analysis of the National Allocation Plans for 27 EU Member States for phase 2 of the EU ETS (2008-2012) suggests that the price and cost effects for improvements in carbon and energy efficiency in the energy and industry sectors will be stronger than in phase 1 (2005-2007), but only because the European Commission has substantially reduced the number of allowances to be allocated by the Member States. To the extent that companies from these sectors (notably power producers) pass through the extra costs for carbon, higher prices for allowances translate into stronger incentives for demand- side energy efficiency. With the cuts in allocation to energy and industry sectors these will be forced to greater reductions, thus the non-ET sectors like household, tertiary and transport will have to reduce less, which is more in line with the cost-efficient share of emission reductions. The findings also imply that domestic efficiency improvements in the energy and industry sectors may remain limited since companies can make substantial use of credits from the Kyoto Mechanisms. The analysis of the rules for existing installations, new projects and closures suggests that incentives for energy efficiency are higher in phase 2 than in phase 1 because of the increased application of benchmarking to new and existing installations and because a lower share of allowances will be allocated for free. Nevertheless, there is still ample scope to further improve the EU ETS so that the full potential for energy efficiency can be realized.
urn:nbn:de:0011-n-1180739
Keywords: 330; Climate policy; emission trading; energy efficiency; innovation